2016
DOI: 10.1002/brb3.505
|View full text |Cite
|
Sign up to set email alerts
|

Review of clinical studies of perampanel in adolescent patients

Abstract: AimTo assess the clinical trial and real‐world data for adjunctive perampanel in adolescents and develop consensus recommendations to guide the use of perampanel in this population in clinical practice.MethodsIn May 2015, 15 epilepsy experts attended a Consensus Development Meeting to assess the clinical trial data for perampanel, specific to the adolescent age group (12‐17 years) and develop consensus treatment recommendations.Results and DiscussionAnalysis of the adolescent subgroup data of three pivotal pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
3
3
0
1
Order By: Relevance
“…Some of the reported increases in body weight could be a result of adolescents maturing. A previous study in adolescent patients with focal seizures showed that the mean change in weight percentile increased slightly from baseline (46.1%) to end of treatment (48.0%) following treatment with adjunctive perampanel (≤12 mg/day) but decreased slightly following treatment with placebo (49.9% to 49.1%); however, as the average weight change observed in adolescents receiving perampanel was consistent with that expected for the general adolescent population, this change can be attributed to normal adolescent growth …”
Section: Discussionsupporting
confidence: 53%
“…Some of the reported increases in body weight could be a result of adolescents maturing. A previous study in adolescent patients with focal seizures showed that the mean change in weight percentile increased slightly from baseline (46.1%) to end of treatment (48.0%) following treatment with adjunctive perampanel (≤12 mg/day) but decreased slightly following treatment with placebo (49.9% to 49.1%); however, as the average weight change observed in adolescents receiving perampanel was consistent with that expected for the general adolescent population, this change can be attributed to normal adolescent growth …”
Section: Discussionsupporting
confidence: 53%
“…Efficacy: The pooled data from the three phase III studies showed improved seizure control in perampanel-treated adolescent, consistent with the overall findings in adults [29,30].…”
Section: Perampanelsupporting
confidence: 77%
“…Due to its novel mechanism of action, perampanel could be considered a rational combination therapy in adolescent patients with focal seizures who have not achieved control with other AEDs . Although the tolerability profile in adolescents was generally favorable in the phase 3 trials, young patients receiving perampanel should be monitored for AEs related to irritability and aggression, particularly during dose titration and at higher doses.…”
Section: Perampanel In Clinical Practicementioning
confidence: 99%